2009
DOI: 10.1177/089686080902900411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Twice-Daily Icodextrin Administration on Blood Pressure and Left Ventricular Mass in Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: Background Hypervolemia is a risk factor for left ventricular hypertrophy and hypertension in peritoneal dialysis patients. Icodextrin improves volume control by increasing ultrafiltration in peritoneal dialysis patients. Aim To examine the effects of twice-daily icodextrin administration on blood pressure and left ventricular hypertrophy in peritoneal dialysis patients with hypervolemia and ultrafiltration failure. Method and Results Administration of icodextrin twice daily resulted in a significant reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…solutions (high transporter), using higher tonicity glucosebased solutions (but this is less preferable), using icodextrin for long day dwell for APD or long overnight dwell for continuous ambulatory PD, restricting dietary salt, and in those with RKF, using diuretics to increase urine volume ( Figure 3). 55,100 Experimental approaches include using a low-sodium dialysate, 101 a bimodal solution with glucose and icodextrin, 102 2 icodextrin exchanges per day, 103 and incorporating intermittent hybrid therapy, all of which require further evaluation. Assessment of membrane function may be considered as adjunctive to clinical measures of UF volume.…”
Section: Hypertension and The Pd Prescriptionmentioning
confidence: 99%
“…solutions (high transporter), using higher tonicity glucosebased solutions (but this is less preferable), using icodextrin for long day dwell for APD or long overnight dwell for continuous ambulatory PD, restricting dietary salt, and in those with RKF, using diuretics to increase urine volume ( Figure 3). 55,100 Experimental approaches include using a low-sodium dialysate, 101 a bimodal solution with glucose and icodextrin, 102 2 icodextrin exchanges per day, 103 and incorporating intermittent hybrid therapy, all of which require further evaluation. Assessment of membrane function may be considered as adjunctive to clinical measures of UF volume.…”
Section: Hypertension and The Pd Prescriptionmentioning
confidence: 99%
“…Maximal UF typically occurs at 10 hours (7), so one may consider a shorter 10-hour icodextrin dwell followed by either a dry period or a 4-6 hour glucose-based exchange as needed to maximize UF. Twice daily icodextrin may enhance fluid removal, but experience is preliminary (8).…”
Section: Optimize Peritoneal Ufmentioning
confidence: 99%
“…39 However, this suggestion was based on three small, low-powered studies. [40][41][42] Another study by Jeloka et al showed that UF does not increase after a 10-hour dwell with icodextrin. 43 Based on this, Dousdampanis and colleagues hypothesized that two 8-hour exchanges with icodextrin could produce more UF than a single 15-16hour exchange.…”
Section: New Osmotic Agentsmentioning
confidence: 99%